Saturation results for the Lagrange max-product interpolation operator based on equidistant knots - Coroianu, Lucian; Gal, Sorin G. (Rev. Anal. Numér. Théor. Approx., 2012)
In this paper we obtain the saturation order and a local inverse result in the approximation by the Lagrange max-product interpolation operator based on equidistant knots.